The discourse of the documentary series "Amazônia Sociedade Anônima" on the Brazilian Amazon (Revista Internacional de Folkcomunicação, 2019)
This paper analyzes the discourse of the documentary series "Amazônia Sociedade Anônima" on the Brazilian Amazon, shown in 2015 by TV Globo's Fantástico program. As a theoretical basis, we refer to Benchimol (2009), Borges (2011), Martino (2007) and others. We used as methodology Bibliographical Research, Documentary and Discourse Analysis (AD) of french line. It is pointed to a romanticization of the Amazonia and to the fact that the social problems and conflicts derived from the aggressions to the environment, to the original, riparian, family and quilombola farmers in the Amazonia are minimized, isolated or treated as irrelevant. Amazonia; Brazil; Series; Fantástico; Discourse.